2021
DOI: 10.3389/fcell.2021.699487
|View full text |Cite
|
Sign up to set email alerts
|

Stress Hormones: Emerging Targets in Gynecological Cancers

Abstract: In the past decade, several discoveries have documented the existence of innervation in ovarian cancer and cervical cancer. Notably, various neurotransmitters released by the activation of the sympathetic nervous system can promote the proliferation and metastasis of tumor cells and regulate immune cells in the tumor microenvironment. Therefore, a better understanding of the mechanisms involving neurotransmitters in the occurrence and development of gynecological cancers will be beneficial for exploring the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…Moreover, systemic use of glucocorticoids could increase the risk for HR-HPV persistence (OR, 2.04; 95% CI, 1.16-3.56) [65]. However, there are still contradictions between experimental and clinical studies on the involvement of glucocorticoids in the development of CxCa [66].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, systemic use of glucocorticoids could increase the risk for HR-HPV persistence (OR, 2.04; 95% CI, 1.16-3.56) [65]. However, there are still contradictions between experimental and clinical studies on the involvement of glucocorticoids in the development of CxCa [66].…”
Section: Discussionmentioning
confidence: 99%
“…Physiological stresses like emotional perturbances, prolonged starvation, and physical trauma can highly disrupt homeostasis and may create a life-threatening condition. Cervical and ovarian cancer are the two major gynecological malignancies of women which are drastically influenced by physiological stressors ( Chen et al., 2021 ). A positive correlation between chronic stress and cervical cancer progression was drawn showed that long-term stress stimuli may activate the sympathetic nervous system and the HPA.…”
Section: Physiological Stress and The Molecular Mechanismmentioning
confidence: 99%
“…They are synthesized by immune and stromal cells, mainly endothelial cells and fibroblasts, and then they regulate cell growth, proliferation, differentiation, cell survival and death, immune cell activation, and cell migration ( Showalter et al., 2017 ). Chronic stressors critically impact on the cytokines profile as compared with chronic stress hormonal signaling ( Chen et al., 2021 ). In particular, the expression of IL-1, IL-2, IL-6, INF-γ, TNF-α, TGFβ, EGF, VEGF, and other growth factors are relatively more associated with chronic conditions as compared to other cytokines ( Ho et al., 2021 ; Lu et al., 2021 ; Zhou et al., 2021 ).…”
Section: Relationship Between Stress and Cytokine Profiles In Cervica...mentioning
confidence: 99%
See 1 more Smart Citation
“…Gynecological malignancies, mainly comprised of cervical, ovarian, and endometrial cancers, contribute immensely to the worldwide cancer load, with cervical cancer being the fourth most common cancer in women ( Bray et al, 2018 ). The high mortality rate of gynecological cancers is majorly due to late diagnosis of the disease, chemoresistance, impaired apoptotic pathway, persistent inflammation, and aberrant MMP production ( Azevedo Martins et al, 2020 ; Carey et al, 2021 ; Chen et al, 2021 ). Inflammation is a process by which the innate immune system reacts to tissue injury or infection by bacteria, viruses, toxins, etc., and facilitates the recruitment of circulating cells by the adaptive immune system to the damaged tissue.…”
Section: Introductionmentioning
confidence: 99%